ELECTROCHEMICAL BEHAVIOR OF CUPRONICKEL ELECTRODE IN ACIDIC MEDIA - R. N. Nurdillayeva; N. Sh. Abdilda; A. B. Bayeshov (Academic Scientific Journal of Chemistry, 2021)
The electrochemical properties of the cupronickel electrode polarized by an alternating current in an aqueous solution of hydrochloric acid were studied for the first time. The electrochemical dissolution of cupronickel was carried out in a polarization mode with a frequency of 50 Hz in pairs with a titanium electrode. The current efficiency of dissolution of Cu-Ni alloys dependence on the current density at the titanium (20-120 kA/m2 ) and cupronickel (200-1200 A/m2 ) electrodes, the concentration of a hydrochloric acid solution (0.5-5.0 M), the electrolysis duration (0.5-1.75 h) and the alternating current effect (50-300 Hz) were considered. It was observed that the current efficiency of the alloy dissolution decreases linearly with increasing current density at the cupronickel electrode, while the current density at the titanium electrode passes through a maximum value at 60 kA/m2 . The dependence of the alloy dissolution on the acid concentration was studied, and the reaction order was calculated. The reaction orders for the formation of copper (I) and nickel (II) ions accounted for 0.95 and 0.85, respectively. As the frequency of the alternating current increased, the current efficiency of the cupronickel electrode dissolution changed significantly. It has been shown that high current frequencies do not provide the required anodic half-cycle duration for the oxidation reaction of the metals, as the periods change very rapidly. It was found that electrolysis is effective at a frequency of 50 Hz AC. It was observed that the dissolution rate of the copper-nickel alloy increases with increasing solution temperature. It was found that the dissolution of cupronickel in an aqueous solution of hydrochloric acid by the temperature-kinetic method takes place in the diffusion-kinetic mode. Ideally, the current efficiency values were 59% for Cu (I) ions and 15% for Ni (II) ions